Sweat testing for the detection of atomoxetine from paediatric patients with attention deficit/ hyperactivity disorder: application to clinical practice. Issue 3 (19th September 2012) - Marchei, Emilia; Papaseit, Esther; Garcia‐Algar, Oscar; Bilbao, Amaia; Farré, Magí; Pacifici, Roberta; Pichini, Simona
Abstract : Atomoxetine (ATX) is a selective norepinephrine reuptake inhibitor approved since 2002 for the treatment of attention deficit hyperactivity disorder (ADHD) in children, adolescents, and adults as an alternative treatment to methylphenidate. Within the framework of a project evaluating the use of alternative biological matrices for therapeutic monitoring of psychoactive drugs in paediatric and non‐paediatric individuals, the excretion of ATX and its principal metabolites has been recently studied in oral fluid and hair. The aim of this study was to describe the excretion profile of ATX and its metabolites 4‐hydroxyatomoxetine (4‐OH‐ATX) and N‐desmethylatomoxetine (N‐des‐ATX) in sweat following the administration of different dosage regimens (60, 40, 35, and 18 mg/day) of ATX to six paediatric patients. Sweat patches were applied to the back of each participant and removed at timed intervals. ATX and its metabolites were measured in patches using a previously validated liquid chromatography‐tandem mass spectrometric (LC‐MS/MS) method. Independently from the administered dose, ATX appeared in the sweat patches 1 h post administration and reached its maximum concentration generally at 24 h. Peak ATX concentrations ranged between 2.31 and 40.4 ng/patch and did not correlate with the administered drug dose, or with body surface area. Total ATX excreted in sweat ranged between 0.008 and 0.121 mg, corresponding to 0.02 and 0.3% of the administered drug. Neither 4‐OH‐ATX, nor N‐des‐ATX was detected in either of the collected sweat patches. Measuring ATX in sweat patches can provide information on cumulative drug use from patch application until removal. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : Atomoxetine (ATX) is a selective norepinephrine reuptake inhibitor approved since 2002 for the treatment of attention‐deficit/hyperactivity disorder (ADHD) in children, adolescents, and adults as alternative treatment to methylphenidate. We studied the excretion profile of ATX and its metabolites 4‐hydroxyatomoxetine (4‐OH‐ATX) and N‐desmethylatomoxetine (N‐des‐ATX) in sweat following the administration of different dosage regimens (60, 40, 35 and 18 mg/day) of ATX to six paediatric patients. Independently from the administered dose, ATX appeared in the sweat patches 1 hour post administration and reached its maximum concentration generally at 24 h. Peak ATX concentrations ranged between 2.31 and 40.4 ng/patch and did not correlate with the administered drug dose, nor with body surface area. Total ATX excreted in sweat ranged between 0.02 and 0.3% of the administered drug. Nor 4‐OH‐ATX‐ or N‐des‐ATX were detected in either of the collected sweat patches.